2017
DOI: 10.4062/biomolther.2016.242
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Autism-Like Behavioral Phenotypes and Postsynaptic Receptors Expression in the Prefrontal Cortex of TERT Transgenic Mice

Abstract: Autism spectrum disorder (ASD) remains unexplained and untreated despite the high attention of research in recent years. Aside from its various characteristics is the baffling male preponderance over the female population. Using a validated animal model of ASD which is the telomerase reverse transcriptase overexpressing mice (TERT-tg), we conducted ASD-related behavioral assessments and protein expression experiments to mark the difference between male and females of this animal model. After statistically anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…These observations were coupled with a reduction of MeCP2 expressions in both the prefrontal cortex of the male offspring and neuronal progenitor cells isolated by sex. We observed the same male bias in the TERT-tg mice, which shows autistic-like phenotypes, more pronounced increase in the expression of VGluT1, a presynaptic marker, and increases in postsynaptic markers of the NMDA and AMPA receptor subtypes [ 209 ].…”
Section: Discussionmentioning
confidence: 83%
“…These observations were coupled with a reduction of MeCP2 expressions in both the prefrontal cortex of the male offspring and neuronal progenitor cells isolated by sex. We observed the same male bias in the TERT-tg mice, which shows autistic-like phenotypes, more pronounced increase in the expression of VGluT1, a presynaptic marker, and increases in postsynaptic markers of the NMDA and AMPA receptor subtypes [ 209 ].…”
Section: Discussionmentioning
confidence: 83%
“…Similar male-specific effects are seen in the telomerase reverse transcriptase overexpressing mice (TERT-tg). Male TERT-tg mice exhibit impaired social behavior, increased anxiety-like behavior, and lowered seizure threshold, while female TERT-tg mice do not (Kim et al, 2017 ). Maternal immune challenge also leads to male-specific deficits in social behavior in the contactin-associated protein-like 2 (Cntnap2) mouse model of ASD (Schaafsma et al, 2017 ).…”
Section: Sex Differences In Glutamate Systems In Diseasementioning
confidence: 99%
“…In addition, telomerase reverse transcriptase-overexpressing (TERT transgenic, TERT-tg) mice exhibit male-specific autism-like behaviors, as well as increases in the expression of the NMDA receptor NR2A and NR2B subunits and AMPA receptor GluR1 and GluR2 subunits. TERT-tg mice also exhibit increases in vesicular glutamate transporter (vGluT) 1 levels in the prefrontal cortex [86]. Furthermore, research has indicated that glutamatergic modulators may aid in the treatment of ASD in humans [83,87] and animal models [85,88,89], supporting the notion that the glutamatergic system plays a role in ASD and ASD-like phenotypes.…”
Section: Altered Expressions Of Genes Related To Excitatory and Inmentioning
confidence: 99%
“…For example, male-biased differences have been observed in patients with ASD exhibiting mutations in genes that encode the synaptic cell adhesion protein neuroligin ( NLGN), including NLGN 3, and NLGN4X [98,99]. Sex-based differences in autistic-like phenotypes have also been reported in animal models of ASD generated by exposure to chemicals or genetic manipulation [8,67,86,100,101,102,103]. For example, Schneider et al [102] demonstrated that prenatal exposure to valproic acid (VPA), which is well known to induce autism-like phenotypes in rats or mice [104], induces some male-specific alterations in behavior and immunological function.…”
Section: Sex-specific Phenotypes Observed In Crmp4-ko Mice and Othmentioning
confidence: 99%
See 1 more Smart Citation